KESENJANGAN KURIKULUM SMK DENGAN KEBUTUHAN INDUSTRI - Sarah Nur Halizah (ADIBA : JOURNAL OF EDUCATION, 2024)
Education within the SMK and vokasi sector entails a holistic educational program aimed at augmenting expertise and knowledge within specific domains. This curriculum predominantly emphasizes practical applications and hands-on experience relevant to various vocations. The alignment with industry requisites is imperative for streamlining industrial operations efficiently and effectively. However, the current SMK curriculum lacks synchronization with the dynamic industrial landscape, raising concerns about its relevance. Hence, there is a pressing need to prioritize the development of the SMK curriculum. This article employs a systematic literature review method to gather data comprehensively. Literature analysis entails scrutinizing pertinent sources to garner insights into specific subjects. The study seeks to comprehend existing literature, research inquiries, and variables. The Indonesian education system distinguishes itself through its emphasis on quality, quantity, locality, and employment aspects. The curriculum serves as a pivotal element in elevating educational standards, constituting the cornerstone of schooling. Ultimately, the overarching aim of education is to enhance the quality of human resources, thereby enriching individual lives and contributing to Indonesian society. In essence, the SMK curriculum plays a pivotal role in elevating educational standards within the SMK and Vokasi sectors.